THE INFLUENCE OF FINANCIAL FACTORS, ESG, AND INFLATION ON STOCK RETURNS IN THE BANKING SECTOR LISTED ON THE IDX IN 2019-2023 - Nabilla Farirah; Agung Putra Raneo; Nyimas Dewi Murnila Saputri (Universitas Airlangga, 2025)
This study aims to determine the effect of financial factors, ESG and inflation on stock returns of banks listed on the IDX in 2019-2023. The sampling method uses a purposive sampling method so that 70 selected samples are obtained from the banking sector listed on the IDX. The regression estimation analysis technique to test the theory and find the relationship between variables uses panel data linear regression with the Common Effect Model. The results of the study show that ROA has a significant effect on stock returns. While LDR, NPL, CAR, ESG and inflation do not have a significant effect on stock returns. LDR, NPL, ROA, CAR, ESG, and inflation have a significant effect on stock returns simultaneously.